Online dynamic equalization adjustment of high-power lithium-ion battery packs based on the state of balance estimation. (15th March 2016) - Wang, Shunli; Shang, Liping; Li, Zhanfeng; Deng, Hu; Li, Jianchao
Highlights: A novel concept (SOB, State of Balance) is proposed for the LIB pack equalization. Core parameter detection and filtering is analyzed to identify the LIB pack behavior. The electrical UKF model is adopted for the online dynamic estimation. The equalization target model is built based on the optimum preference. Comprehensive imbalance state calculation is implemented for the adjustment. Abstract: A novel concept named as state of balance (SOB) is proposed and its online dynamic estimation method is presented for the high-power lithium-ion battery (LIB) packs, based on which the online dynamic equalization adjustment is realized aiming to protect the operation safety of its power supply application. The core parameter detection method based on the specific moving average algorithm is studied because of their identical varying characteristics on the individual cells due to the manufacturing variability and other factors, affecting the performance of the high-power LIB pack. The SOB estimation method is realized with the detailed deduction, in which a dual filter consisting of the Unscented Kalman filter (UKF), equivalent circuit model (ECM) and open circuit voltage (OCV) is used in order to predict the SOB state. It is beneficial for the energy operation and the energy performance state can be evaluated online prior to the adjustment method based on the terminal voltage consistency. The energy equalization is realized that is based on the credibility reasoning together with the equalization model building process. The experiments including the core parameter detection, SOB estimation and equalization adjustment are done and the experimental results are analyzed. The experiment results show that the numerical Coulomb efficiency is bigger than 95%. The cell voltage measurement error is less than 5 mV and the terminal voltage measurement error of the LIB pack is less than 1% FS. The measurement error of the battery discharge and charge maintenance current is less than 1% FS. The SOB estimation error is less than 5% in the laboratory room, the temperature of which is about 25 °C. The equalization charging current is 2 A and the equalization discharging current is 4.4 A, which can realize the real-time energy equalization adjustment among the connected cells in the LIB pack, guaranteeing its safety in the power supply application.